Did the global financial crisis hit Africa? Insights from a multi-country firm level survey - Duygun, Meryem; Isaksson, Anders; Kaulich, Florian (Elsevier, 2016)
In order to craft the most appropriate policy responses, it is imperative to identify the degree to which the firms in sub-Saharan Africa (SSA) were affected by the global financial crisis, despite the common perception amongst macro analysts that the global financial crisis was mainly confined to industrialized countries, as opposed to countries in the SSA. Whilst macro figures for various reasons might not display strong signs of financial crisis, because of mitigating effects in sectors less integrated in the world economy, directly interviewing private sector firms in SSA reveals a very different reality. We use a new and unique cross-sectional firm-level dataset mainly collected in 2010 covering some 19 countries and about 2,500 firms and show that SSA countries were indeed affected by the financial crisis. Our results also suggest that productivity levels, labour and TFP, are significantly important indicators for the probability of whether a plant will feel the ramifications of an exogenous shock like the recent financial crisis. Other important variables identified are firms’ per worker levels of human and physical capital, size and age. Moreover, we find strong evidence for the role of trade as a transmission channel of the crisis, as it carries over from northern economies to SSA. It turns out that invoking the destination of exports into the analysis is crucial for understanding how African countries were affected by the crisis.